ANALISIS BEBAN KERJA PETANI PADA PENGOLAHAN LAHAN STROBERI DI KABUPATEN TABANAN - ., M. Yusuf; ., Nyoman Adiputra; Sutjana, I Dewa Putu; ., Ketut Tirtayasa (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 2 No 2 (2016): Volume 2 No 2 Desember 2016, 2016)
Bedugul is a village in Tabanan regency that produce strawberry. Bedugul is famous tourist area not only in Bali or Indonesia, are even known in the world. . In the process of planting strawberries, farmers cultivate land by making raised beds (bedeng) beforehand, add fertilizer, coat beds with mulch, and make a hole in the plastic mulch. there are problems in the processing of these strawberry fields, such as the musculoskeletal disorder and general fatigue. This research was conducted observational against 12 strawberry farmers in Bedugul Tabanan regency. The workload is predicted by calculated the pulse that measured by ten pulse methode in artery radialis use a stopwatch. Ambient temperature and humidity are measured with a sling psychrometer.  Wind speed is measured using the anemometer. Temperature heat of solar radiation measured with a thermometer bulb. General fatigue predicted by 30 item questioners about fatigue with 4 Likert scale. Musculoskeletal disorders predicted by Nordic Body Map. ECPT (extra calorie due to peripheral temperature) and ECPM (extra calorie due to peripheral metabolism) is calculated based on the pulse restore of the farmers. The results of this research concluded that: (1) Workload strawberry farmers categories of heavy workload, (2) There are significant differences in the score of subjective disorder of farmers (musculoskeletal disorder and general fatigue) before and after work, (3) The value of ECPM higher than ECPT so that to improve the activity of the farmers can be done through the task of strawberry farmers (4) score RULA analysis values obtained grand score of 7, that is mean investigation and change are required immediately. It is therefore recommended to immediate improvement in the work of the strawberry farmers
Keywords: workload, musculoskeletal disorder, general fatigue, ECPT, ECPM